Avenues in seed and planting material production in floriculture - Kumar, Ramesh; Kumar, Anshul (Indian Horticulture, 2024)
Floriculture, a vital part of horticulture, involves cultivating, processing and marketing ornamental plants. This industry’s heart lies in the production of high- quality seeds and planting materials, which are crucial for ensuring consistent quality, disease resistance and optimal yield. High-quality planting material in floriculture is required by commercial growers, nurseries, landscapers, researchers, amateur growers and the floriculture export industry. Techniques such as hybrid seed production, vegetative propagation and specialized structures like bulbs and corms are widely used, while advanced methods like micropropagation and genetic improvements enable large-scale, disease-free plant production. Though India imports much of its flower seed material, it has significant potential to boost domestic production and export capabilities. Beyond flowers, the production and marketing of seeds and planting materials present valuable growth opportunities. Key challenges, including genetic purity, disease management and adherence to phytosanitary regulations, must be addressed.